Modern American Drama - David, Sister M. Agnes S.S.J. (New York The Macmillan Company, 1961)
You, the reader, will shape the play in your own mind as you read. What the play means to you-what you get out of it-depends upon the curiosity, the alertness, and the sympathy with which you read it.
Keywords: Literature